STUDI KUALITATIF: GAMBARAN PSIKOLOGIS IBU POSTPARTUM DENGAN HIV/AIDS DI PUSKESMAS SENTANI - Utami, Arum Surya; Lestari, Susi (Ensiklopedia Research and Community Service Review, 2025)
Abstract: The postpartum period (puerperium) is the period after labor and delivery of a baby and the recovery period, starting from the completion of labor until the reproductive organs return to their pre-pregnancy state, which takes a varying amount of time between 6-12 weeks. During the postpartum period, physiological changes in the body will occur and psychological changes in the mother will occur regarding the baby she has given birth to (Hutabarat, 2021). For health issues, one of the issues that is still a global concern is the spread of the HIV virus. Individuals who are HIV and AIDS positive will experience changes in their lives. WHO says that when individuals are first diagnosed with HIV, most show changes in their psychosocial character such as living in stress, depression, feeling a lack of social support, and changes in behavior. The purpose of this study is to provide a picture of the psychological state of postpartum mothers with HIV/AIDS at the Sentan Health Center. The research method is descriptive qualitative. The results of this study are a picture of the psychology of postpartum mothers in the form of stress and sadness responses experienced by postpartum mothers with HIV/AIDS. This is a psychological disorder that is naturally felt by mothers during the postpartum period. Moreover, the mother is infected with HIV/AIDS. By not abandoning God and surrendering, you can calm the mood of postpartum mothers who suffer from HIV/AIDS a little.Keywords: HIV/AIDS